Determinismo biológico e educação sexual : análise retórica da concepção da sexualidade em livros didáticos - Piovezan, Gustavo (2010)
Biology begins his story with the theoretical research on heredity in Ancient Greece. However, it was only through the advent of the theories of evolution in the nineteenth century, the investigations of biological knowledge tended toward an improvement and structuring of its body of theory or, in the words of Kuhn, began the process of normal science. During the period covered the years 1920-1980, many studies in biology have, thanks to the thought causal / deterministic milestones in the history of Western society, in this particular case of this study: gender preconception and the strengthening of a dominant ideology guided the heteronormative model company still remaining in science education - one rooted eugenic thinking, but supported in research on sexuality, behavior, IQ and genetics. Beginning in 1960 with the development of a theoretical corpus of feminist studies, sexuality began to understand factors such as the concept of gender, which showed the complexity of the matter, while the ideology of male domination in society until then (LOURO, 1997). In this context, biology was the science in which feminist scholarship and gender had the greatest impact. In the epistemological sense, a case constitutes the phenomenon of bacterial reproduction: the reading and description of this phenomenon can be compromised when performed in a heterosexual perspective. Already a policy perspective, the genre provides for equality between women and men. Therefore, based on the idea that the influence of gender in science is a phenomenon, this research aimed to make a rhetorical analysis of the conception of sexuality in teaching materials science. The reason is the same: sexuality, gender differences and their representation in the contents regarding sexuality in the manuals of science and biology. This idea arises from the curricular proposals expressed in the National Curriculum Parameters for Secondary Education (PCN). In discussing gender, sexuality and education within the school context the PCN are the first document of reference in Brazilian politics. In the light of gender studies the concept of sex is replaced by the concept of gender as a result of a number of implications. The concept of gender is connected to different sexual orientations, the different male and female gender and different identities of the subjects. It was under this aegis that we start the analysis, using rhetoric as a method. We focus on the French rhetorical tradition, builds upon the works of Chaim Perelman. The object of analysis, in turn, was to find the meaning that the arguments and figures of speech of teaching materials science and biology contained. The text proceeds in four parts: first, an introduction where we situate the context of the discussion, the second part, we emphasize the importance of feminist studies and gender to epistemology and political economy of science and the relationship of these factors on education science. In the third part, the analysis has some examples of content analysis and, finally, the fourth part, our final considerations.